On the Macroeconomic Consequences of Over-Optimism - Beaudry, Paul (IMF Working Papers; Working Paper ;, 2018)
Is over-optimism about a country's future growth perspective good for an economy, or does over-optimism also come with costs? In this paper we provide evidence that recessions, fiscal problems, as well as Balance of Payment-difficulties are more likely to arise in countries where past growth expectations have been overly optimistic. To examine this question, we look at the medium-run effects of instances of over-optimism or caution in IMF forecasts. To isolate the causal effect of over-optimism we take an instrumental variables approach, where we exploit variation provided by the allocation of IMF Mission Chiefs across countries. As a necessary first step, we document that IMF Mission Chiefs tend to systematically differ in their individual degrees of forecast-optimism or caution. The mechanism that transforms over-optimism into a later recession seems to run through higher debt accumulation, both public and private. Our findings illustrate the potency of unjustified optimism and underline the importance of basing economic forecasts upon realistic medium-term prospects.